Sistem pengurusan kualiti keperluan (semakan kedua ) (ISO 9001 : 2015, IDT) (Diterbitkan oleh Jabatan Standard Malaysia pada tahun 2017) (Malaysian Standard MS ISO 9001 :2015 (BM), 2017)
a Benefit of certification : - QMS will help you to better manage your business to meet customer requirements. This will result in better products, better customer service, satisfied customer and repeat orders - With proper implementation of the systems, your business will become more efficient and productive thus will reduce errors and rework, reduce operation cost, time and use of resources - The systems promote continual improvement, which will provide your business with the competitive edge to compete in the market place and for those who have succeeded, to become more successful and resilient - The systems also look into the needs of your human resource which will also increase staff morale and commitment - Complying to standards provide you with the accolades for competitive edge - All of the above will increase profitability